FORMATION OF HEALTH CULTURE IN FUTURE THERAPY AND REHABILITATION SPECIALISTS (Physical Culture and Sport: Scientific Perspective, 2024)
The article deals with the urgent problem of fostering a culture of health. Nowadays, a large number of studies are devoted to this topic, as it has become more relevant than ever. The level of health culture formation in future specialists in therapy and rehabilitation is determined.It specifies various approaches to the issue of health preservation by future therapy and rehabilitation specialists based on the analysis of literary sources. The fact that these specialists help to restore health, means they should be able to apply methods of a consistent and continuous rehabilitation process. Such a process takes place subject to the accumulation of knowledge of the biomedical, psychological, pedagogical and sports and pedagogical cycle of disciplines mastered by a future specialist in therapy and rehabilitation while studying at a university. It is in the process of training that a therapy and rehabilitation specialist must learn not only to apply the acquired knowledge in the course of their work, but also to use it in their own daily life. It is substantiated that constant stress, the global environmental crisis, epidemics, and eventually war have become the reality every modern Ukrainian student has to face. Such conditions undoubtedly affect the state of the young body. And not only on the physical component of health, but also on the psychological state and relationships of a young person in society. Based on a questionnaire conducted with students majoring in Therapy and Rehabilitation, the article shows the level of health culture, healthy lifestyle, and understanding of the importance of using health technologies in the life of future professionals. In conclusion, recommendations are given on what should be paid special attention to in order to form a culture of health in future specialists in therapy and rehabilitation.
Keywords: health culture; specialist; therapy; rehabilitation; health-saving technologies; healthy lifestyle; educational environment